Unmasking the Persona: A Barthesian Semiotic Study of Ahmad Dhani’s Instagram Self-Branding - Darmawan, Tjiong Natanael Hanny; Linuwih, Endar Rachmawaty; Renfei, Xiao (English Department, Universitas Negeri Surabaya, 2025)
Social media platforms provide celebrities with strategic opportunities to construct and project identities, yet studies employing semiotic frameworks remain limited. This research investigates how Indonesian musician and public figure Ahmad Dhani constructs self-branding through a single Instagram post, analyzed using Roland Barthes’ semiotic theory. Employing a qualitative case study, the study examines how visual and textual elements interact to create layered meanings across denotation, connotation, and myth. The findings reveal that Dhani’s post—featuring orchestral imagery and the textual message “Sorry if I am different”—functions not as an apology but as an affirmation of uniqueness. At the denotative level, the tuxedo, conductor’s stance, and blurred audience emphasize authority, refinement, and public recognition. Connotatively, the warm color palette and self-referential caption highlight creativity and authenticity. At the mythic level, the post transforms perceived arrogance into a narrative of leadership, positioning Dhani as a visionary figure whose difference signifies intellectual depth and cultural capital. This analysis underscores how Instagram can serve as a site for myth-making, where visual and textual signs operate as strategic tools for personal branding and reputation management. While the study offers insights into the cultural work of celebrity self-representation, its scope is limited to a single post. Future research should extend this analysis to multiple figures and longitudinal datasets to capture the evolving dynamics of digital identity construction.